Efectos de los probióticos (Lactobacillus acidophilus y Bifidobacterium spp), y temperaturas de maduración en las características organolépticas del salami - Delgado Castillo, Eduardo José (2014)
The research was performed to evaluate the effects of probiotics (Lactobacillus acidophilus and Bifidobacterium spp.) using meat product at different ripeness temperature. A salami was used to improved organoleptic characteristics. DCA bifactorial 2*3 was applied to the salami to see different affects that would have. Six treatments and three replicates were used, plus a witness. Using 5 kg of salami for each treatment. For the experiment, the salamis were made with two types of probiotics: Lactobacillus acidophilus and Bifidobacterium spp., and then introduced to three different temperatures: 16 ºC, 18 ºC and 20 ºC. We assessed physical - chemical variables: Weight Loss (INEN 464), pH (INEN 389) and microbiological: Coliform (INEN 1529-7), Salmonella (INEN 1529-1515), Fungi and Yeasts (INEN 1529-1510). Depending on these variables and sensory analysis it was established that the best form of introducing probiotics were the combinations a1b1 (Lactobacillus acidophilus at a temperature of 16 °C) and a1b2 (Lactobacillus acidophilus at a temperature of 18 °C), at those temperatures we produced high amounts of organoleptic characteristics, with high amounts of probiotic present, free of pathogens, weight loss values and pH. The parameters were pointed out by the NTE INEN 1343 (Meat and meat products. Salami, requirements).